2013
DOI: 10.1016/j.bbrc.2012.11.137
|View full text |Cite
|
Sign up to set email alerts
|

Proteasome inhibitor MG132 induces NAG-1/GDF15 expression through the p38 MAPK pathway in glioblastoma cells

Abstract: The expression of nonsteroidal anti-inflammatory drug-activated gene-1 (NAG-1) is regulated by the p53 and Egr-1 tumor suppressor pathways. Many anti-cancer drugs and chemicals induce NAG-1 expression, but the mechanisms are not fully understood. Transgenic mice expressing human NAG-1 are resistant to intestinal and prostate cancer, suggesting that NAG-1 is a tumor suppressor. Proteasome inhibitors exhibit anti-glioblastoma activities in preclinical studies. Here, we show that the proteasome inhibitors MG132 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 20 publications
1
21
0
1
Order By: Relevance
“…Expression of GDF15 and miR-3189-3p Is Increased after Fenofibrate Treatment-Previous reports have demonstrated that GDF15 expression is induced following treatment by a variety of chemotherapeutic agents (13,21,22). In line with these findings, we have also reported that this gene is up-regulated in a microarray analysis of glioblastoma cells treated with the metabolically active anticancer compound fenofibrate (4).…”
Section: Role Of Sf3b2 and P63rhogef In The Inhibition Of Cellular Prsupporting
confidence: 85%
“…Expression of GDF15 and miR-3189-3p Is Increased after Fenofibrate Treatment-Previous reports have demonstrated that GDF15 expression is induced following treatment by a variety of chemotherapeutic agents (13,21,22). In line with these findings, we have also reported that this gene is up-regulated in a microarray analysis of glioblastoma cells treated with the metabolically active anticancer compound fenofibrate (4).…”
Section: Role Of Sf3b2 and P63rhogef In The Inhibition Of Cellular Prsupporting
confidence: 85%
“…These genes are known to play roles in neural development [51, 52]. GDF15 has also been shown to induce apoptosis and inhibit tumorigenesis in GBM [53, 54]. …”
Section: Resultsmentioning
confidence: 99%
“…As well as the observed increase in E11 protein expression, we also revealed that Bortezomib/ALLN/MG132 increased E11 mRNA levels. In other studies MG132 and Bortezomib have been reported to induce mRNA increases through both transcriptional (promoter activation) and post‐transcriptional (mRNA stability) mechanisms (Butler et al, ; Laroia et al, ; Shimizu et al, ). Conversely, MG132 causes defective polyadenylation (Lee and Moore, ) and whilst it has been previously shown that in human tissues, there is a 2.7 kb and a 0.9 kb E11 mRNA species, which differ in their polyadenylation (Martin‐Villar et al, ), there is no suggestion that this is the case in murine tissues.…”
Section: Discussionmentioning
confidence: 95%